PENGEMBANGAN MEDIA PEMBELAJARAN SIGAP TERHADAP HASIL BELAJAR PEMAHAMAN KONSEP IPA - A. Nur Azizah Asfin; Ferdiansyah, Handy; Takdir, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the SIGAP learning media and test its validity, practicality, and effectiveness on students' conceptual understanding of science concepts in seventh-grade students at the UPT SMP Negeri 1 Panca Rijang. This study employed a mixed methods approach with an exploratory sequential design and a Research and Development (R&D) methodology that applied the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Qualitative data were obtained through observation and interviews, while quantitative data were obtained through questionnaires, tests, and validation sheets. The study subjects consisted of two validators (a material expert and a media expert), one science teacher, and 109 students as a sample of 164 students. The effectiveness test used a one-group pretest-posttest design. The results showed that the SIGAP learning media was categorized as